Graphite-loaded tin fluoride nano-composite high-performance lithium storage negative electrode material as well as preparation method and application thereof
SnF2 is mixed with graphite by ball milling to prepare graphite-loaded tin fluoride nanocomposite material, which solves the problem of complex preparation and poor performance of tin fluoride composite materials in the prior art, and realizes the preparation of high-performance lithium storage negative electrode materials, which is suitable for lithium-ion batteries.
Patent Information
- Application Number
- CN202411761566.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-04
AI Technical Summary
The method for preparing tin fluoride composite materials in the prior art is complex in operation, poor performance, and nano-scale products have limitations in industrial applications, making it difficult to achieve the synthesis of controlled morphology, size and chemical composition.
SnF2 was mixed with graphite by ball milling, and its molar ratio and particle size were adjusted to prepare a SnF2 nanocomposite material evenly coated with graphite.
The high lithium storage reversibility and ultra-high capacitive lithium storage of SnF2/C composite materials in lithium-ion batteries are achieved, providing higher capacity and better cycle stability, and the process is simple and low cost, which is suitable for large-scale production.
Smart Images

Figure CN119764370A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery electrode materials, and in particular to a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material and a preparation method and application thereof. Background Art
[0002] Nanostructured metal fluorides and semiconductor materials are highly desirable for advanced electronic, magnetic, optoelectronic and sensing applications. Metal fluorides have great potential for application in batteries as nanostructured materials. By precisely controlling the synthesis and structural design of metal fluorides, battery performance optimization and customized design can be achieved. Tin-based fluorides have attracted much attention as anode materials for lithium-ion batteries (LIBs) due to their high specific capacity. In particular, tin-based anode materials have a high specific capacity of 994 mAh g -1 The highest theoretical specific capacity is graphite (372 mAh g -1 ), which is 2.6 times higher than commercial carbon negative electrode materials.
[0003] Recently, several synthetic routes have been successfully used to synthesize SnF2 nanostructures. Sofiane Bouazza et al. used commercially available tin fluoride (II) recrystallization to prepare nanocrystalline SnF2 as anode material for lithium-ion batteries. -1 The capacity after 30 cycles at a current density of 557 mAh g -1 (Materials Letters, 2011, 65, 1334-1336); Ghulam Ali et al. used SnF2 / acetylene black composites prepared by ball milling process as negative electrode materials for sodium ion batteries. -1 The capacity after 50 cycles at the current density is 337 mAh g -1 (Nano Energy, 2017, 42, 106-114); Muhammad Ashfaq Jamil et al. used ball milling to prepare SnF2 / C nanocomposites as negative electrode materials for lithium-ion batteries. -1 The capacity after 100 cycles at the current density is 768 mAh g -1 (Journal of Alloys and Compounds, 2022, 900, 163447). However, the tin fluoride composite material synthesized by the above conventional method is complicated to operate and has unsatisfactory performance.
[0004] In summary, the methods for preparing tin fluoride composite materials reported in existing literature are slightly complicated and the performance is not superior, and nanoscale products have limitations in industrial applications. The synthesis of SnF2 nanostructures with controlled morphology, size, chemical composition and a large amount is a key step towards nano applications. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material and a preparation method and application thereof.
[0006] The technical solution adopted by the present invention is as follows:
[0007] The first aspect of the present invention provides a method for preparing a graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material, comprising the following steps:
[0008] S1: SnF2 is mixed with graphite, and ball-milled in a ball mill to obtain a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material, wherein the mesh size of the graphite is 30 to 70 meshes, and the molar ratio of SnF2 to graphite is 3 to 5:1.
[0009] Preferably, in step S1, the mesh size of graphite is 50 meshes.
[0010] Preferably, in step S1, the molar ratio of SnF2 to graphite is 4:1.
[0011] Preferably, in step S1, the mesh size of SnF2 is 400-600 mesh.
[0012] Preferably, in step S1, ball milling is performed in a ball milling jar at a rotation speed of 300 to 500 rpm for 20 to 28 hours.
[0013] The second aspect of the present invention provides a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material obtained by the preparation method described above.
[0014] The third aspect of the present invention provides a lithium-ion battery, which uses the graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material as the negative electrode material.
[0015] Preferably, the preparation method comprises the following steps:
[0016] (A) weighing graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material, Ketjen black and polyvinylidene fluoride, adding N-methylpyrrolidone, mixing evenly, grinding and stirring into a paste, and applying the paste onto a copper foil;
[0017] (B) Drying, slicing, assembling and pressing the copper foil coated with the negative electrode material to obtain the lithium ion battery.
[0018] The beneficial effects of the present invention are as follows: The present invention specifically uses a ball milling method to mix SnF2 and graphite for ball milling, and prepares SnF2 nanoparticles by comparative ratio and mesh screening to obtain a SnF2 nanocomposite material uniformly coated with graphite, and its electrochemical properties have high lithium storage reversibility and ultra-high capacitive lithium storage. This method provides lithium-ion batteries with higher capacity and better cycle stability. Compared with existing reports, the preparation method of the present invention is simple in process, low in cost, easier to mass produce, and the obtained SnF2 / C composite material has excellent cycle performance and rate performance in lithium-ion batteries.
[0019] The SnF2 / C composite material obtained in one embodiment of the present invention is used as a negative electrode of LIB at 100 mA g -1 After 120 cycles, the capacity is as high as 1219.5 mAh g -1 , at 1000mA g -1 The capacity is as high as 1023.7 mAh g after 500 cycles at current -1 , the performance is significantly higher than the results of published articles in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0021] Figure 1 Scanning electron microscope (SEM) images (ac) of the graphite sheet encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode material prepared in Example 1 of the present invention;
[0022] Figure 2 The scanning electron microscope (SEM) images of the graphite sheet encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode materials prepared in Comparative Examples 1, 2, 3 and 4 of the present invention are (ac), (df), (gi) and (jl), respectively;
[0023] Figure 3 X-ray diffraction patterns of graphite sheet encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention;
[0024] Figure 4The graphite sheet encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode material prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention is subjected to 100 mA g -1 Cyclic stability test diagram under current density;
[0025] Figure 5 The graphite sheet encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode material prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention is subjected to 1000 mA g -1 Cyclic stability test diagram under current density;
[0026] Figure 6 The graphs are rate cycling performance diagrams of graphite sheet-encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention at different current densities. DETAILED DESCRIPTION
[0027] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0028] Example 1
[0029] The present embodiment provides a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material, and the preparation method thereof comprises the following steps: S1, weighing 0.08g 500-mesh SnF2 and 0.02g 50-mesh graphite, putting them into a stainless steel ball mill, and ball milling them at a speed of 350rpm for 24h to obtain a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material.
[0030] Comparative Example 1
[0031] The present embodiment provides a graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material, and the preparation method thereof comprises the following steps: S1, weighing 0.1 g of 500 mesh SnF2, putting it into a stainless steel ball mill, and ball milling it at a speed of 350 rpm for 24 hours to obtain a graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material.
[0032] Comparative Example 2
[0033] The present embodiment provides a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material, and the preparation method thereof comprises the following steps: S1, weighing 0.08g 500-mesh SnF2 and 0.02g 20-mesh graphite, putting them into a stainless steel ball mill, and ball milling them at a speed of 350rpm for 24h to obtain a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material.
[0034] Comparative Example 3
[0035] The present embodiment provides a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material, and the preparation method thereof comprises the following steps: S1, weighing 0.08g 500-mesh SnF2 and 0.02g 200-mesh graphite, putting them into a stainless steel ball mill, and ball milling them at a speed of 350rpm for 24h to obtain a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material.
[0036] Comparative Example 4
[0037] The present embodiment provides a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material, and the preparation method thereof comprises the following steps: S1, weighing 0.08g 500-mesh SnF2 and 0.02g 325-mesh graphite, putting them into a stainless steel ball mill, and ball milling them at a speed of 350rpm for 24h to obtain a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material.
[0038] Application Examples
[0039] The graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode materials prepared in the above Example 1 and Comparative Examples 1-3 are respectively assembled into lithium-ion batteries by the following method, and the assembly method comprises the following steps:
[0040] (A) Weigh graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material, Ketjen black and polyvinylidene fluoride in a mass ratio of 7:2:1, add an appropriate amount of N-methylpyrrolidone, mix well, grind and stir into a paste, and apply it on a copper foil;
[0041] (B) Drying, slicing, assembling and pressing the copper foil coated with the negative electrode material to obtain the lithium ion battery.
[0042] Microscopic characterization
[0043] The following are the microscopic characterization results of different methods for the graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode materials prepared in Example 1 and Comparative Examples 1-3:
[0044] Figure 1Scanning electron microscope (SEM) images (ac) of the graphite sheet encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode material prepared in Example 1 of the present invention; By comparison, it can be seen from the SEM that the particle size of the sample in Example 1 is finer, which provides a larger surface area to increase the contact area between the electrolyte and the electrode material, thereby accelerating ion transmission, and the smaller particle size means that the ion diffusion path is shortened, thereby achieving faster lithium ion transmission. In addition, the particle size of the tin fluoride composite 50 mesh graphite is also relatively uniform, and the uniform particle size of the powder can also more effectively reduce the damage to the material structure caused by volume expansion.
[0045] Figure 2 Scanning electron microscope (SEM) images (a1) of graphite sheets encapsulating tin fluoride nanocomposite high-performance lithium storage negative electrode materials prepared in Comparative Examples 1, 2, 3 and 4 of the present invention; it can be seen from SEM that Comparative Example 1 presents irregular large blocks and dispersed particles; the sample in Comparative Example 2 presents uneven particle size, and the particle size is generally large, which may be due to the large particle size of the ball-milled 20-mesh graphite itself and the small ball milling effect; the particle size of Comparative Example 3 is different, and the small particle size is unevenly dispersed, and is also thinner and larger than the particle size of the composite 325-mesh graphite in Comparative Example 4. By comparison, it can be seen that the effect of ball-milled tin fluoride composite 50-mesh graphite is better, and the tin fluoride nanoparticles are evenly dispersed in the graphite.
[0046] Figure 3 X-ray diffraction patterns of graphite sheet-encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention.
[0047] Electrochemical performance characterization
[0048] Figure 4 The graphite sheet encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode material prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention is subjected to 100 mA g -1 Cyclic stability test diagram under current density; By comparing the cyclic stability performance diagram, it can be seen that the tin fluoride composite 50 mesh graphite lithium storage negative electrode material of Example 1 is at 100mA g -1 At this current density, after 120 cycles, there is still 1219.5 mAh g -1 Comparative Example 1SnF2 pure lithium storage negative electrode material at 100mA g -1 At this current density, after 120 cycles, the current density was only 243.5 mAh g -1 Comparative Example 2 Tin fluoride composite 20 mesh graphite lithium storage negative electrode material at 100mA g -1At this current density, after 120 cycles, the current density is only 357.6 mAh g -1 Comparative Example 3 Tin fluoride composite 200 mesh graphite lithium storage negative electrode material at 100mA g -1 At this current density, after 120 cycles, it is only 668.8 mAh g -1 Comparative Example 4 Tin fluoride composite 325 mesh graphite lithium storage negative electrode material at 100mA g -1 At this current density, after 100 cycles, the current is only 566.2 mAh g -1 This indicates that 50-mesh graphite loaded with tin fluoride has ultra-high capacitive lithium storage.
[0049] Figure 5 The graphite sheet encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode material prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention is subjected to 1000 mA g -1 Cyclic stability test diagram under current density; By comparing the cyclic stability performance diagram, it can be seen that the tin fluoride composite 50 mesh graphite lithium storage negative electrode material of Example 1 is at 1000mA g -1 At the current density, after 500 cycles, there is still 1023.7 mAh g -1 Comparative Example 1SnF2 pure lithium storage negative electrode material at 1000mA g -1 At this current density, after 500 cycles, the current is only 237.8 mAh g -1 Comparative Example 2 Tin fluoride composite 20 mesh graphite lithium storage negative electrode material at 1000mA g -1 At this current density, after 500 cycles, the current is only 377 mAh g -1 Comparative Example 3 Tin fluoride composite 200 mesh graphite lithium storage negative electrode material at 1000mA g -1 At this current density, after 500 cycles, the current is only 318.9 mAh g -1 Comparative Example 4 Tin fluoride composite 325 mesh graphite lithium storage negative electrode material at 1000mA g -1 At this current density, after 500 cycles, the current is only 567.7 mAh g -1 This indicates that 50-mesh graphite encapsulated tin fluoride has ultra-high capacitive lithium storage.
[0050] Figure 6 The graph of the rate cycling performance of the graphite sheet encapsulated tin fluoride nanocomposite high-performance lithium storage negative electrode material prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 at different current densities; at different rates, the current density of 50 mesh graphite loaded with tin fluoride returned to 100 mA g after 80 cycles -1 In this case, the capacity can return to 1414.5mAh g -1; and at 1000, 2000 and 5000mA g -1 After 10 cycles at high current density, the capacities are maintained at 1015.4, 932.4, and 770 mAh g, respectively. -1 Comparative Example 1: The current density of pure tin fluoride lithium storage negative electrode material returned to 100 mA g after 80 cycles. -1 The case capacity is only 590.4mAh g -1 , and at 1000, 2000 and 5000mA g -1 At high current density, the capacity is only 345.7, 264.9 and 136.3 mAh g -1 Comparative Example 2: Tin fluoride composite 20 mesh graphite lithium storage negative electrode material cycles 80 times and the current density returns to 100 mAg -1 The case capacity is only 700.3mAh g -1 , and at 1000, 2000 and 5000mA g -1 At high current density, the capacity is only 394.4, 254.5 and 88.4 mAh g -1 Comparative Example 3: Tin fluoride composite 200 mesh graphite lithium storage negative electrode material cycles 80 times and the current density returns to 100 mA g -1 Case capacity is 1158mAh g -1 , and at 1000, 2000 and 5000mA g -1 At high current density, the capacity is only 754.7, 651 and 507 mAh g -1 Comparative Example 4: Tin fluoride composite 325 mesh graphite lithium storage negative electrode material cycles 80 times and the current density returns to 100 mA g -1 The case capacity is only 831.6mAh g -1 , and at 1000, 2000 and 5000mA g -1 At high current density, the capacity is only 401.8, 297.7 and 15.4 mAh g -1 The results show that the 50-mesh graphite sheet uniformly encapsulates tin fluoride nanoparticles as lithium storage material and has high lithium storage reversibility when used as the negative electrode of lithium-ion batteries.
[0051] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A method for preparing a graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material, characterized in that: The steps include: S1: SnF2 is mixed with graphite, and ball-milled in a ball mill to obtain a graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material, wherein the mesh size of the graphite is 30 to 70 meshes, and the molar ratio of SnF2 to graphite is 3 to 5:
1.
2. The method for preparing a graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material according to claim 1, characterized in that: In step S1, the mesh size of graphite is 50 meshes.
3. The method for preparing a graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material according to claim 1, characterized in that: In step S1, the molar ratio of SnF2 to graphite is 4:
1.
4. The method for preparing a graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material according to claim 1, characterized in that: In step S1, the mesh size of SnF2 is 400-600 meshes.
5. The method for preparing a graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material according to claim 1, characterized in that: In step S1, ball milling is performed in a ball milling jar at a rotation speed of 300 to 500 rpm for 20 to 28 hours.
6. A graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material obtained by the preparation method according to any one of claims 1 to 5.
7. A lithium ion battery, characterized in that: It adopts the graphite-loaded tin fluoride nanocomposite high-performance lithium storage negative electrode material as claimed in claim 5 as the negative electrode material.
8. A lithium ion battery according to claim 7, characterized in that: The preparation method thereof comprises the following steps: (A) weighing graphite-supported tin fluoride nanocomposite high-performance lithium storage negative electrode material, Ketjen black and polyvinylidene fluoride, adding N-methylpyrrolidone, mixing evenly, grinding and stirring into a paste, and applying the paste onto a copper foil; (B) Drying, slicing, assembling and pressing the copper foil coated with the negative electrode material to obtain the lithium ion battery.
Citation Information
Patent Citations
Preparation method of tin carbon composite material for negative electrode of lithium ion batteries
CN102185135A
Modified graphene composite lithium-ion battery anode material and preparation method thereof
CN108539184A
Catalytic SnO2-Fe-C lithium ion battery anode material and preparation method thereof, and application of Catalytic SnO2-Fe-C lithium ion battery anode material
CN110429259A
Anode material for secondary battery,secondary battery including the anode material and method for preparing the anode material
US20180034044A1